Impact of rare variants in ARHGAP29 to the etiology of oral clefts: role of loss‐of‐function vs missense variants. Issue 5 (26th July 2016) - Savastano, C.P.; Brito, L.A.; Faria, Á.C.; Setó‐Salvia, N.; Peskett, E.; Musso, C.M.; Alvizi, L.; Ezquina, S.A.M.; James, C.; GOSgene,; Beales, P.; Lees, M.; et al.
Abstract : Non‐syndromic cleft lip with or without cleft palate (NSCL/P) is a prevalent, complex congenital malformation. Genome‐wide association studies (GWAS) on NSCL/P have consistently identified association for the 1p22 region, in which  ARHGAP29 has emerged as the main candidate gene. ARHGAP29 re‐sequencing studies in NSCL/P patients have identified rare variants; however, their clinical impact is still unclear. In this study we identified 10 rare variants in ARHGAP29, including five missense, one in‐frame deletion, and four loss‐of‐function (LoF) variants, in a cohort of 188 familial NSCL/P cases. A significant mutational burden was found for LoF (Sequence Kernel Association Test, p = 0.0005) but not for missense variants in  ARHGAP29, suggesting that only LoF variants contribute to the etiology of NSCL/P. Penetrance was estimated as 59%, indicating that heterozygous LoF variants in ARHGAP29 confer a moderate risk to NSCL/P. The GWAS hits in  IRF6 (rs642961) and 1p22 (rs560426 and rs4147811) do not seem to contribute to the penetrance of the phenotype, based on co‐segregation analysis. Our data show that rare variants leading to haploinsufficiency of ARHGAP29 represent an important etiological clefting mechanism, and genetic testing for this gene might be taken into consideration in genetic counseling of familial cases. Abstract :